BATIK DAN KONTRIBUSINYA TERHADAP PEREKONOMIAN NASIONAL - Ulum, Ihyaul (Jurnal Bestari, 2009)
Batik is typical cultural heritage of Indonesia. The history of its existence and growth cannot be argued. Batik has existed since Majapahit empire era and then expanding right at the period of Mataran empire, Solo, and Yogyakarta. Not only in Java, batik has also grown and expanded in Sumatra Island. Moreover, the confession of UNESCO on October, 2nd 2009 that batik is genuine and intangible cultural heritage of Indonesia has revoked Malaysia?s claim as batik heir and owner. More than simply cultural heritage, batik has also transformed into industry with high contribution to national economy. Furthermore, the number of labours in this group of industry (TPT) is 1.62 million people indeed. The value of batik export even reached US$ 32.28 million in 2008, and US$ 10.86 million in the first three months of 2009.